Afrikaans First Additional Language teachers’ experiences teaching online during COVID-19 at two public high schools in Gauteng, South Africa - Nesta Drake; Geoffrey Vaughan Lautenbach (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Due to the COVID-19 pandemic, schools across South Africa were forced to turn to online education. As with other subjects, Afrikaans First Additional Language (AFAL) teachers had to find ways to continue teaching their learners online under COVID-19 restrictions. For many, this was a daunting task and unfamiliar territory. This research explores how AFAL teachers from two public schools in Gauteng Province experienced online teaching during COVID-19. For this research, seven participants were selected through purposive sampling to participate in either semi-structured individual interviews or a focus group. Additional data was gathered from various documents from the two schools. Analysis of the data demonstrated that online communication created several barriers while teaching. In addition, learners' poor work ethic had a ripple effect, and work provided online had to be retaught once learners returned to school. Although teaching AFAL online is not necessarily the recommended approach, there are certain advantages to incorporating online platforms in a classroom setting. Despite various challenges, teachers continued to provide learners with work while trying to make an abnormal situation as normal as possible.